2014
DOI: 10.1080/10408398.2011.619671
|View full text |Cite
|
Sign up to set email alerts
|

Immune System Stimulation by Probiotic Microorganisms

Abstract: Probiotic organisms are claimed to offer several functional properties including stimulation of immune system. This review is presented to provide detailed informations about how probiotics stimulate our immune system. Lactobacillus rhamnosus GG, Lactobacillus casei Shirota, Bifidobacterium animalis Bb-12, Lactobacillus johnsonii La1, Bifidobacterium lactis DR10, and Saccharomyces cerevisiae boulardii are the most investigated probiotic cultures for their immunomodulation properties. Probiotics can enhance non… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
234
0
16

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 413 publications
(272 citation statements)
references
References 111 publications
3
234
0
16
Order By: Relevance
“…The daily use of the probiotics Lactobacillus rhamnosus HN001 and Bifidobacterium lactis by the mother before delivery and during lactation showed significant increase in neonate cord blood cytokine (IFN-γ) as well as in IgA in breast milk [32]. A recent study showed a significant increase in phagocytic activity of blood leukocytes after three weeks of milk probiotics consumption or the consumption of probiotics-supplemented milk for nine weeks by healthy elderly persons.…”
Section: Probiotics and Immune Systemmentioning
confidence: 97%
See 3 more Smart Citations
“…The daily use of the probiotics Lactobacillus rhamnosus HN001 and Bifidobacterium lactis by the mother before delivery and during lactation showed significant increase in neonate cord blood cytokine (IFN-γ) as well as in IgA in breast milk [32]. A recent study showed a significant increase in phagocytic activity of blood leukocytes after three weeks of milk probiotics consumption or the consumption of probiotics-supplemented milk for nine weeks by healthy elderly persons.…”
Section: Probiotics and Immune Systemmentioning
confidence: 97%
“…A recent study showed a significant increase in phagocytic activity of blood leukocytes after three weeks of milk probiotics consumption or the consumption of probiotics-supplemented milk for nine weeks by healthy elderly persons. Also, it showed a significant increase of T lymphocytes and Natural Killer [32].…”
Section: Probiotics and Immune Systemmentioning
confidence: 98%
See 2 more Smart Citations
“…Health benefits include: controlling gastrointestinal infections, improvement in lactose metabolism, anticarcinogenic and antimutagenic properties, reduction in serum cholesterol, and improvement in inflammatory bowel disease, Helicobacter pylori infections, and immune system stimulation [6].…”
Section: Introductionmentioning
confidence: 99%